Konsep Diri, Adversity Quotient dan Penyesuaian Diri pada Remaja - Bariyyah Hidayati, Khoirul; ., M Farid (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2016)
The Orphanage youths usually has the ability of lower self adoption compared than the most of youths. This research done to know how the self concept interaction and adversity quotient with the self adoption of the orphanage youths are. The research subjects are 50 Muhammadiyah orphanage youths of Probolinggo. They consist of male and female are about 15-16 years old. Data of self concept, adversity quotient and the self adoption of the orphanage youths are acquired by using scale. The analyses test result between the variable of self concept , adversity quotient and the self adoption with The regretful analyses result acquired from F=96,076 with p/sig =0,000 (p<0,01) that means there’s a significant correlation in a such collective way between the self concept and adversity quotient with the self adoption. Acquired r2=0,803 that means the self concept and adversity quotient with the self adoption give a contribution 80,30% to te self adoption of youths. Then, it’s Acquired t=13,097 and r partial 0,886 with p/sig =0,000 (p<0,01) that means there’s a significant positive correlation between the self concept with the self adoption of youths. It’s acquired t=0,041 and r partial =0,006 with p/sig=0,968 (p>0,05) so there isn’t any correlation between adversity quotient and th self adoption of youths.Keywords : self concept, adversity quotient, self adoption of the youths